Determination of Community Readiness and Participation Post-Social Forestry Permit: Analysis of Internal and External Factors - Suryaningsih, Suryaningsih (Adabi : Journal of Public Administration and Business, 2024)
The Indonesian government persistently advocates for advancing social forestry initiatives as a component of economic equalization and forest conservation strategies. At the local level, particularly within Lima Puluh Kota Regency, the execution of this policy encounters various challenges. The substantial achievements in the area designated for social forestry do not correspond with the community's preparedness and engagement in managing the permits that have been allocated. This research aims to elucidate the community's readiness and involvement in the stewardship of social forestry post-permit acquisition. This investigation's adopted methodological framework is qualitative and centered around case studies. Data analysis will incorporate triangulation techniques to enhance the validity of the findings. The study's findings reveal that the community's readiness and participation following permit acquisition in Lima Puluh Kota Regency is notably insufficient, influenced by internal and external factors. Internal factors encompass a deficiency in knowledge and comprehension, economic constraints, and limitations within local institutions. External factors comprise inadequate budget allocations from the government, non-governmental organizations, and donor agencies, restricted market access and infrastructure, the predominance of local elites, and reliance on external support.